(3QSGdI GdeSHMjI hCe GdbdGFO GdfScjI hbGeYI GdYbGFO GdTQcjIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdefRg Yf GdYOO hGdhdO Edi LejY ef JbQH Edi GddGghJ HMbjbjI GdbQHGf hJeSc Hg ef cd Cgd GdMb s
(3BNQgG (B:s
(3hdG aSNf GdebGdGJ GdeNJdbI Ydi eSjM GdMb HGdTQYjI GdecPhHI Ydi Cgd GdMb ai cd OgQ hChGf JeJ Hefg hdi GdBNQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B54s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis